Seroconversion of red blood cell antibody in ABO-incompatible living donor liver transplantation -a case report - Lee, Eun Kyung; Song, Insun; Kim, Gaab Soo (Korean journal of anesthesiology, 2020)
Liver transplantation usually requires blood transfusion, and a red blood cell (RBC) antibody screen is essential for the prevention of a hemolytic reaction. Since proper ABO-compatible grafts are lacking, ABO-incompatible living donor liver transplantation (ABO-i LDLT) with desensitization is a feasible therapy. Desensitization includes intravenous rituximab injection and plasmapheresis before surgery.BACKGROUNDLiver transplantation usually requires blood transfusion, and a red blood cell (RBC) antibody screen is essential for the prevention of a hemolytic reaction. Since proper ABO-compatible grafts are lacking, ABO-incompatible living donor liver transplantation (ABO-i LDLT) with desensitization is a feasible therapy. Desensitization includes intravenous rituximab injection and plasmapheresis before surgery.A 60-year-old female was diagnosed with hepatitis B virus-related hepatocellular carcinoma and planned for ABO-i LDLT. She tested positive in a RBC antibody screen over two years; however, she tested negative for the test after desensitization. Clinicians noted the seroconversion during induction, and thus, a delay in the preparation of adequate packed RBC was unavoidable.CASEA 60-year-old female was diagnosed with hepatitis B virus-related hepatocellular carcinoma and planned for ABO-i LDLT. She tested positive in a RBC antibody screen over two years; however, she tested negative for the test after desensitization. Clinicians noted the seroconversion during induction, and thus, a delay in the preparation of adequate packed RBC was unavoidable.Even when the latest RBC antibody screen is negative after immunosuppression, clinicians should consider the possibility of a prior positive result to promote safer medical treatment and management.CONCLUSIONSEven when the latest RBC antibody screen is negative after immunosuppression, clinicians should consider the possibility of a prior positive result to promote safer medical treatment and management.